Radiation dose reduction in cerebral CT perfusion imaging using iterative reconstruction. - Niesten, Joris M; van der Schaaf, Irene C; Riordan, Alan J; de Jong, Hugo W A M; Horsch, Alexander D; Eijspaart, Daniel; Smit, Ewoud J; Mali, Willem P T M; Velthuis, Birgitta K (European Radiology, 2014)
Objectives: To investigate whether iterative reconstruction (IR) in cerebral CT perfusion (CTP) allows for 50% dose reduction while maintaining image quality (IQ).Methods: A total of 48 CTP examinations were reconstructed into a standard dose (150 mAs) with filtered back projection (FBP) and half-dose (75 mAs) with two strengths of IR (middle and high). Objective IQ (quantitative perfusion values, contrast-to-noise ratio (CNR), penumbra, infarct area and penumbra/infarct (P/I) index) and subjective IQ (diagnostic IQ on a four-point Likert scale and overall IQ binomial) were compared among the reconstructions.Results: Half-dose CTP with high IR level had, compared with standard dose with FBP, similar objective (grey matter cerebral blood volume (CBV) 4.4 versus 4.3 mL/100 g, CNR 1.59 versus 1.64 and P/I index 0.74 versus 0.73, respectively) and subjective diagnostic IQ (mean Likert scale 1.42 versus 1.49, respectively). The overall IQ in half-dose with high IR level was scored lower in 26-31%. Half-dose with FBP and with the middle IR level were inferior to standard dose with FBP.Conclusion: With the use of IR in CTP imaging it is possible to examine patients with a half dose without significantly altering the objective and diagnostic IQ. The standard dose with FBP is still preferable in terms of subjective overall IQ in about one quarter of patients.Key Points: • Computed tomography perfusion (CTP) is increasingly important in ischaemia imaging. • Radiation exposure of CTP is a drawback. • Iterative reconstruction (IR) allows reduction of radiation dose in unenhanced head CT. • CTP IR enables 50% dose reduction without altering objective and diagnostic quality.